PENDEKATAN PENDIDIKAN NILAJ SECARA KOMPREHENSIF SEBAGAI SUATU ALTERNATIF PEMBENTUKAN AKHLAK BANGSA - Darmiyati Zuchdi, Darmiyati Zuchdi (Jurnal Cakrawala Pendidikan, 2016)
The eclining quality of the Indonesian character needs to be resolved. One of the ways to solve this problem is through the educational practice, by using a more effective approach. A single approach of values education is considered to be ineffective, that is why it is needed a comprehensive one. The development of students’ personality should be holistic in nature, including the intellectual, emotional, and spiritual intelligence. Four important substances of values education are values realization, character education, citizenship education, and moral education. Various programs are needed to help young people develop their "life skills". The important goals of character education include: respect, responsibility, compassion, self-discipline, loyalty, courage, tolerance, work ethic, and a belief in and love of God. The major aspects of citizenship education include: knowledge of being good citizens, appreciation to democratic system and civic values, critical thlnking skills, communication skills, cooperation skills, and conflict resolution skills. The major goal of moral education is to produce autonomous individuals who are in a high level of moral reasoning, are colnlnitted to acting in a manner cosistent with it or who have noble characters. The four important substances stated above are better integrated in Religion Education and Pancasila Moral Education. Various strategies of values and moral education should be utilized, including inculcating values, modeling values, facilitating values, and the development of skills for achieving a personally peaceful and socially constructive life, as a manifestation of strong faith.